2022
DOI: 10.1111/mice.12831
|View full text |Cite
|
Sign up to set email alerts
|

Visual–inertial structural acceleration measurement

Abstract: Structural vibration measurement is a crucial and necessary step for structural health monitoring. Recently, computer vision-based techniques have been proposed by researchers to measure structural motion remotely. However, the direct application of vision-based measurement to practical applications still faces some challenges, mainly because intrinsic camera vibration can introduce significant errors to the measurement results. In this study, a three-stage approach using an embedded inertial measurement unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The analysis revealed that several sensors had been used for validation purposes, including laser displacement sensors [32,34,41,42,49,70,74,76,82], accelerometers [32][33][34]50,51,53,55,59,61,[64][65][66][67][68]76], IMU [60], linear variable differential transformers [34,36,41,50,54,61,66,67,73], laser Doppler vibrometers [38,46], stationary cameras [42,75,83], actuators [71], laser trackers [81], infrared sensors [48], and marker-based systems [44,73]. Marker-based systems are routinely used in other fields (such as medicine), where they are the traditional reference systems for motion capture and analysis.…”
Section: Validation With Gold-standardmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that several sensors had been used for validation purposes, including laser displacement sensors [32,34,41,42,49,70,74,76,82], accelerometers [32][33][34]50,51,53,55,59,61,[64][65][66][67][68]76], IMU [60], linear variable differential transformers [34,36,41,50,54,61,66,67,73], laser Doppler vibrometers [38,46], stationary cameras [42,75,83], actuators [71], laser trackers [81], infrared sensors [48], and marker-based systems [44,73]. Marker-based systems are routinely used in other fields (such as medicine), where they are the traditional reference systems for motion capture and analysis.…”
Section: Validation With Gold-standardmentioning
confidence: 99%
“…This choice applies to the following studies: [34,[40][41][42]44,45,[48][49][50][51][53][54][55][58][59][60][61][62][63][64]66,67,[69][70][71][72][73][74][75][76][77][78][80][81][82]. In a few cases, the experimental scenarios were outdoors where, on the other hand, it was necessary to consider, at least in part, the environmental conditions and the problems previously indicated, testing the solution on scale models in most cases as well.…”
Section: Experimental and Real-world Scenariosmentioning
confidence: 99%
“…Weng et al. (2022) used a complementary filter with an adaptive gain to estimate the 3‐DOF camera rotations from the IMU measurements. Although this technique no longer needs to find the stationary points in the camera field of view (FOV), it has the disadvantages of high cost and an accumulative measurement error over time (Kok et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (2021) used certain numerical integration techniques to estimate the translations and rotations of the UAV from the data of acceleration and angular velocity recorded by accelerometers and gyroscopes, respectively. Weng et al (2022) used a complementary filter with an adaptive gain to estimate the 3-DOF camera rotations from the IMU measurements. Although this technique no longer needs to find the stationary points in the camera field of view (FOV), it has the disadvantages of high cost and an accumulative measurement error over time (Kok et al, 2017).…”
mentioning
confidence: 99%